A case of lymphosarcoma in a local Indian dairy cross cow - Sheikh Omar, Abdul Rahman; Ng, B. K. Y.; Salim, N. (Persatuan Doktor Veterinar Malaysia, 1980)
A case of lymphosarcoma of the Enzootic Bovine Leukosis type was seen in a Local Indian Dairy Cross cow in a milking herd in Serdang, There was a persistent leucocytosis in excess of 100,000 per cu mm of which 95 percent were lymphocytes. The lesion was multicentric in distribution involving most lymph nodes, thymus, spleen, abomasum and liver, Histologically, the neoplastic cells resembled lymphocytes. The importance of this disease in the Malaysian context is briefly discussed.